2019
DOI: 10.23917/indigenous.v3i2.6591
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Social Support And Psychological Well-Being Among Interstate Students At Malikussaleh University

Abstract: This study aims to examine the relationship between perceived social support and psychological well-being among interstate students at Malikussaleh University, Lhokseumawe. It is hypothesized that there will be positive relationship between perceived social support and psychological well-being. As the second largest state university in Aceh, students at Malikussaleh University come from different parts of Aceh and Indonesia. Thus, it is important to understand their psychological well-being as it will help the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
1
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 13 publications
3
20
1
7
Order By: Relevance
“…Berbagai penelitian tentang kesejahteraan psikologis menunjukkan bahwa kesejahteraan psikologis dipengaruhi oleh kepribadian (Hicks & Mehta, 2018), religiusitas (Harpan, 2015), status sosial (Fassbender & Leyendecker, 2018), dan dukungan sosial (Adyani, Suzanna, Safuwan, & Muryali, 2018). Terutama bagi mahasiswa, dukungan sosial merupakan faktor yang penting bagi kesejahteraan psikologis mahasiswa (Z.…”
Section: Pendahuluanunclassified
See 3 more Smart Citations
“…Berbagai penelitian tentang kesejahteraan psikologis menunjukkan bahwa kesejahteraan psikologis dipengaruhi oleh kepribadian (Hicks & Mehta, 2018), religiusitas (Harpan, 2015), status sosial (Fassbender & Leyendecker, 2018), dan dukungan sosial (Adyani, Suzanna, Safuwan, & Muryali, 2018). Terutama bagi mahasiswa, dukungan sosial merupakan faktor yang penting bagi kesejahteraan psikologis mahasiswa (Z.…”
Section: Pendahuluanunclassified
“…Korelasi positif antara kesejahteraan psikologis dan dukungan sosial pada mahasiswa telah ditemukan dalam berbagai penelitian (Adyani et al, 2018;Triaswari & Utami, 2014;Yasin & Dzulkifli, 2010). Kesejahteraan psikologis mahasiswa mengalami peningkatan seiring dengan diterimanya dukungan sosial.…”
Section: Pendahuluanunclassified
See 2 more Smart Citations
“…13 Psychological well-being is an important aspect in one's life as it is refers to positive mental health Psychological well-being is often defined as some combination of positive affective states such as happiness and functioning with optimal effectiveness in individual and social life. 14 Kadiyono, Anissa and Harding and Diana conducted a research entitled Religiosity and Psychological Well-Being: Implication to Improve Disaster Management. The results showed that their psychological well-being is in moderate low category.…”
Section: Discussionmentioning
confidence: 99%